Molting drives mortality in foraging populations of Formosan subterranean termites (Isoptera: Rhinotermitidae) baited with a chitin synthesis inhibitor, noviflumuron. Issue 1 (26th September 2017) - Kakkar, Garima; Su, Nan‐Yao
Abstract : This study examines the impact of termite molting behavior on Coptotermes formosanus (Shiraki) colony elimination when treated with noviflumuron. Workers fasting period can extend the elimination time by one molt cycle. Abstract: BACKGROUND: The lethal time of a chitin synthesis inhibitor (CSI)‐baited colony of Coptotermes formosanus Shiraki largely depends on the time taken for workers to molt after consuming a lethal dose. Given that termite molting biology can regulate the time to elimination of a baited termite colony, the objective of this study was to determine how the fasting period (an important element of the worker molting cycle) and acquisition of the lethal dose can impact the total elimination period for a colony. RESULTS: Noviflumuron eliminated the foraging population over a 30 m‐long foraging arena within 9 weeks. However, mortality in treatment groups did not begin until day 11. The 10‐day lag post treatment corresponds to the fasting period during which workers to prepare for ecdysis on the 11th day, at which time mortality occurs due to the effect of CSI. CONCLUSION: This study shows that, with the exception of successful molting events during the first 10 days after baiting, mortality among workers is inevitable in the next molt with lethal doses of noviflumuron. The 10‐day fasting period can comprise at least 22% of a molt cycle (45 days for a fourth worker instar or lower), and can provide a window during which a worker escapes the effect of CSI bait, thereby extending the total time needed for elimination of a colony. © 2017 Society of Chemical Industry